EVALUATING SCHOLARLY OPINIONS ON THE USE OF ISHARI METHODOLOGY IN QUR'ANIC VERSE INTERPRETATION - Zakaria, Siti Nora’Aeshah; Mat Said, Mohamad Hilmi; Mohd Azmi, Mohammad Haafiz Aminuddin (Jurnal 'Ulwan, 2025)
Ishari Interpretation refers to the symbolic or implicit methodology used in the exegesis of Qur'anic verses. This method of interpretation is predominantly associated with Sufi traditions. However, it has generated significant controversy among scholars. Therefore, this study aims to analyze the views of both traditional and modern scholars regarding the permissibility of interpreting Qur'anic verses using the Ishari methodology. The study employs a qualitative approach with primary data obtained through document analysis. The data is analyzed using content analysis methods. Key themes to address the research questions have been identified through coding. The study reveals three scholarly opinions on the permissibility of using Ishari interpretive methodology. First, some scholars disapprove of Ishari interpretation, considering it a deviation from proper exegesis. Second, some scholars fully endorse it, while the third group permits it under specific conditions. Based on these three viewpoints, the author selects the third opinion as the most accurate and meticulous, capable of preventing deviations in Qur'anic interpretation. The conditions imposed by this opinion help prevent the widespread emergence of erroneous exegesis.